Effect of systemic antibiotic therapy on pulp repair following extrusive luxation and avulsion in a murine model: A histomorphological study - Queiroz, Alfredo Franco [UNESP]; Hidalgo, Mirian Marubayashi; Consolaro, Alberto; Barioni, Sônia Regina Panzarini [UNESP]; França, Alline Batistussi [UNESP]; Melo, Moriel Evangelista [UNESP]; Poi, Wilson Roberto [UNESP] (My University, 2022)
Background/Aim: The evidence for any benefit of systemic antibiotic therapy on pulp survival following extrusive luxation and avulsion is inconclusive. The aim of this study was to evaluate the effect of systemic antibiotic therapy with amoxycillin and tetracycline for 7 days on different aspects of dental pulp repair in a murine model. Material and Methods: The right maxillary incisor of 180 4 to 8-week-old male Wistar rats underwent extrusive luxation or avulsion. The animals were then treated with saline solution (control), tetracycline, or amoxicillin administered intra-gastrically for 7 days, and euthanized at 7, 15, and 30 days post-operatively. The layer of odontoblast cells, reparative dentin deposition, Hertwig's epithelial root sheath, pulp necrosis, and periapical inflammatory infiltrate were histomorphologically analyzed and scored. Mann–Whitney, Kruskal–Wallis, and Dunn tests were used to compare mean scores for the different procedures, treatments, and times (p ≤.05). Results: Significant differences were observed between luxated and avulsed teeth (p <.05). In luxated teeth, no differences were observed among treatments and times, except for more tertiary dentin deposition in the coronal third with the use of tetracycline compared with amoxicillin at 15 days (p <.05). In avulsed teeth, higher scores for the layer of odontoblast cells and lower scores for periapical inflammatory infiltrate at 7 days and pulp necrosis at 7 and 15 days were observed in the amoxicillin group compared to the saline and tetracycline groups (p <.05). At 30 days, however, no differences were observed among treatments. Conclusions: The use of systemic antibiotic therapy with tetracycline or amoxicillin for 7 days did not contribute to pulp repair following extrusive luxation or avulsion in rats. However, the results warrant further research into the use of amoxicillin for a more extended period of time in cases of avulsion.
Keywords: amoxicillin; animal model; dental pulp; tetracycline; tooth replantation; tooth repositioning